Numerical Analysis Of The Effects Of Transient Aerodynamics On Driving Stability - Cheng, See Yuan; Tsubokura, Makoto; Nakashima, Takuji; Okada T.; Nouzawa, Takahide (2011)
The present study investigated the effects of transient aerodynamic forces on driving stability of road vehicle. The investigation was carried out using large eddy simulation (LES). To facilitate the investigation, two vehicle models with distinct upper body geometries were developed. The models adopted the characteristic geometries of upper body of real sedan-type vehicles with distinct pitching stability behavior. To probe the dynamic response of the models, a forced-sinusoidal-pitching oscillation is imposed on them during the LES. Accordingly, the models undergo pitching oscillation in a similar manner to the rear-ride-height fluctuation of real vehicles. To allow quantitative analysis on the stability characteristic of models, a parameter termed aerodynamic damping coefficient is introduced. The coefficient quantifies the work done by aerodynamic pitching moment on the models during pitching oscillation. For validation of the LES method, flow structures around the models obtained by stationary LES were compared to the wind tunnel measurements. The comparison shows good agreement. Meanwhile, the dynamic LES results show higher aerodynamic damping in the model with rounded front pillar configuration, by about 22.3%. The Underbody has the highest contribution to the total aerodynamic damping, which was up to 69%. However, the difference between the aerodynamic damping of models with distinct front and rear pillar configurations mainly depends on the trunk-deck contribution.